Literature Review : Analisis Faktor-Faktor Yang Mempengaruhi Kejadian Musculoskeletal Disorders (Msds) Pada Pekerja di Sektor Manufaktur - Oktavia, Ratih; Susilawati, Susilawati (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
Musculoskeletal Disorders (MSDs) are health problems experienced by a person in his musculoskeletal system, which includes muscles, nerves, tendons, joints, cartilage and spinal discs. The World Health Organization (WHO) reports that Musculoskeletal Disorders (MSDs) are the most common condition related to occupational diseases, which are estimated to account for 60% of all occupational diseases. This study aims to identify the factors that affects the incidence of Musculoskeletal Disorders (MSDs). This research uses the literature review method, with information sources taken from Google Scholar and Semantic Scholar in the 2019-2024 time frame. The journals obtained were selected based on predetermined criteria, and after the screening process, 16 articles were obtained that met these criteria. The results of the literature review stated that there are 2 types of risk factors that cause musculoskeletal disease, namely factors from individuals and factors from work. Individual factors include age, gender, Body Mass Index (BMI), exercise habits and posture. Then work factors include work period, work posture, workload, work duration and work attitude.